Cover Image. Issue 9 (September 2017) - Jaruga, Pawel; Coskun, Erdem; Kimbrough, Kimani; Jacob, Annie; Johnson, W. Edward; Dizdaroglu, Miral
Abstract : The cover image, by Pawel Jaruga et al., is based on the Research Article Biomarkers of oxidatively induced DNA damage in dreissenid mussels: A genotoxicity assessment tool for the Laurentian Great Lakes, DOI:10.1002/tox.22427 .